Communication in high risk ante-natal consultations: a direct observational study of interactions between patients and obstetricians - Jo Hilder; Maria Stubbe; Lindsay Macdonald; Peter Abels; Anthony C. Dowell (BMC, 2020)
Abstract Background Effective communication is crucial to any doctor-patient consultation, not least in pregnancy where the outcome affects more than one person. While higher levels of patient participation and shared decision making are recognised as desirable, there is little agreement on how best to achieve this. Most previous research in this area is based on reported data such as interviews or surveys and there is a need for more fine-grained analysis of authentic interaction. This study aimed to identify the discourse characteristics and patterns that exemplify effective communication practices in a high-risk ante-natal clinic. Methods We video-recorded 20 consultations in a high-risk ante-natal clinic in a large New Zealand city with patients attending for the first time. Post-consultation interviews were conducted with the 20 patients and 13 obstetricians involved. Discourse analysis of the transcripts and videos of the consultations was conducted, in conjunction with thematic analysis of interview transcripts. Results Most patients reported high quality communication and high levels of satisfaction; the detailed consultation analysis revealed a range of features likely to have contributed. On the clinician side, these included clear explanations, acknowledgement of the patient's experience, consideration of patient wishes, and realistic and honest answers to patient questions. On the patient side, these included a high level of engagement with technical aspects of events and procedures, and appropriate questioning of obstetricians. Conclusions This study has demonstrated the utility of combining direct observation of consultations with data from patient experience interviews to identify specific features of effective communication in routine obstetric ante-natal care. The findings are relevant to improvements needed in obstetric communication identified in the literature, especially in relation to handling psychosocial issues and conveying empathy, and may be useful to inform communication training for obstetricians. The presence of the unborn child may provide an added incentive for parents to develop their own health literacy and to be an active participant in the consultation on behalf of their child. The findings of this study can lay the groundwork for further, more detailed analysis of communication in ante-natal consultations.